My tummy hurts – a case report of abdominal pain and macrocytic anemia caused by hypothyroidism. (23rd August 2018) - Hamid, Kewan; Dayalani, Neha; Jabbar, Muhammad; Saah, Elna
Summary: A 6-year-old female presented with chronic intermittent abdominal pain for 1 year. She underwent extensive investigation, imaging and invasive procedures with multiple emergency room visits. It caused a significant distress to the patient and the family with multiple missing days at school in addition to financial burden and emotional stress the child endured. When clinical picture was combined with laboratory finding of macrocytic anemia, a diagnosis of hypothyroidism was made. Although chronic abdominal pain in pediatric population is usually due to functional causes such as irritable bowel syndrome, abdominal migraine and functional abdominal pain. Hypothyroidism can have unusual presentation including abdominal pain. The literature on abdominal pain as the main presentation of thyroid disorder is limited. Pediatricians should exclude hypothyroidism in a patient who presents with chronic abdominal pain. Contrast to its treatment, clinical presentation of hypothyroidism can be diverse and challenging, leading to a delay in diagnosis and causing significant morbidity. Learning points: Hypothyroidism can have a wide range of clinical presentations that are often nonspecific, which can cause difficulty in diagnosis. In pediatric patients presenting with chronic abdominal pain as only symptom, hypothyroidism should be considered by the pediatricians and ruled out. In pediatric population, treatment of hypothyroidism varies depending on patients' weight and age. Delay in diagnosis of hypothyroidism can cause significant morbidity and distress in pediatrics population.